KURIKULUM PENDIDIKAN ISLAM PERSPEKTIF AL-QUR’AN DAN HADIS - Daris Salama Ulin Nuha; Imroatul Hasanah; Halimatus Sa'diyah; Muhammad Hori (As-Sulthan Journal of Education, 2026)
This study aims to examine the concept of the Islamic education curriculum from the perspective of the Qur’an and Hadith as fundamental guidelines for shaping the religious character of learners. The curriculum in Islamic education functions not only as a tool for organizing learning activities but also as an instrument for instilling the values of faith, worship, and morality in a balanced manner between worldly and spiritual needs. Using a qualitative research method with a library research approach, this study analyzes primary and secondary literature through processes of identification, classification, interpretation, and synthesis. The findings indicate that the Islamic education curriculum is built upon three fundamental concepts—ta’lim, tarbiyah, and ta’dib—each encompassing cognitive, affective, and psychomotor dimensions. In addition, the characteristics of the Islamic curriculum must reflect a balance between intellectuality, spirituality, morality, and the social needs of learners. The Qur’an and Hadith provide a strong foundation for curriculum components such as the teaching of monotheism (tauhid), the integration of Islam–Faith–Excellence (Islam–Iman–Ihsan), morality, as well as the inclusion of social sciences and natural sciences. This study affirms that a curriculum grounded in revealed values is capable of shaping individuals who possess Islamic character, noble morality, and comprehensive intellectual abilities. Therefore, the Islamic education curriculum must be designed systematically to remain responsive to contemporary developments without departing from the principles of the Sharia.